Histories of teachers in Australia and New Zealand from the 1970s to the present. Issue 2 (26th September 2019) - Whitehead, Kay
Abstract : Purpose: Commencing with publications in the 1970s, the purpose of this paper is to review the historical writing about Australian and New Zealand teachers over the past 50 years. Design/methodology/approach: The paper incorporates men and women who led and taught in domestic spaces, per-school, primary, secondary and higher education. It is structured around publications in the ANZHES Journal and History of Education Review, and includes research published in other forums as appropriate. The literature review is selective rather than comprehensive. Findings: Since the 1980s, the history of New Zealand and Australian teachers has mostly focussed on women educators in an increasing array of contexts, and incorporated various theoretical perspectives over time. Originality/value: The paper highlights key themes and identifies potential directions for research into Australian and New Zealand teachers.